Analyzing Interaction between Seeds and Pre-Seeding Treatment Machines of Cyclic Action* - V. P. Zabrodin; M. V. Sukhanova (Сельскохозяйственные машины и технологии, 2019)
Damage and destruction of seeds by working parts of agricultural machinery affects the quality of future harvest. Presowing treatment of seeds is carried out, as a rule, with machines of periodic cyclic action. (Research purpose) To determine the degree of damage caused to seeds during pre-sowing treatment with chemical and biological dressing agents in cyclic machines, to analyze the interaction processes between seeds and working parts of pre-sowing treatment machines of cyclic action. (Materials and methods) The authors examined possible options of sequencing the interaction between working parts of machines and seeds and determined the shock mechanical impact on seeds made by working parts. Basing on research results obtained by other scientists as well as a wide range of theoretical and experimental studies and the best available practices, the authors have made a comparative analysis of the existing technological solutions. (Results and discussion) The authors have examined the effect of working parts on the degree of damage caused to seeds at various stages of pre-sowing treatment: while loading, mixing, and unloading. (Conclusions) The most sparing technological process has been identified, including loading the drum with a bucket elevator and unloading the material into piles or elastic containers. In this case, damage caused to grain seeds will amount to 2.2-4.5 percent, and those of legumes – not more than 6 percent. It is recommended not to use auger loaders and paddle mixers when designing cyclic machines, since they cause severe damage to seeds, especially those of legumes, of up to 20-32 percent. The seed damage rate can be decreased due to the use of modern materials featuring high elasticity and capable of withstanding considerable stretching within the limits of elastic deformations.